2021
DOI: 10.1111/jcmm.16418
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐122 promotes apoptosis of keratinocytes in oral lichen planus through suppressing VDR expression

Abstract: Oral lichen planus (OLP), a common immune-mediated disease, shows oral ulceration and persistent inflammation in patients those who experience discomfort and remarkable impairments of oral functioning and life quality. 1 Albeit OLP is regarded as an inflammatory disorder, malignant transformation rate of OLP is approximately 1.4% within 7 years. 2 Ulceration, gender and location on the tongue are key risky factors responsible for malignant transformation. 2 There are six subtypes of OLP in clinic, including at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In our previous explorations, we found that vitamin D concentration in the serum derived from OLP patients is decreased relative to that from healthy controls 16 . In addition, we provided robust evidence that vitamin D/vitamin D receptor (VDR) pathway curbs cell apoptosis and pro‐inflammatory cytokine production in oral keratinocytes under inflammatory condition via regulating miRNAs, HIF‐1α signalling and renin levels 19–24 . However, the effect of vitamin D on STING and its downstream cytokines remains an enigma.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In our previous explorations, we found that vitamin D concentration in the serum derived from OLP patients is decreased relative to that from healthy controls 16 . In addition, we provided robust evidence that vitamin D/vitamin D receptor (VDR) pathway curbs cell apoptosis and pro‐inflammatory cytokine production in oral keratinocytes under inflammatory condition via regulating miRNAs, HIF‐1α signalling and renin levels 19–24 . However, the effect of vitamin D on STING and its downstream cytokines remains an enigma.…”
Section: Introductionmentioning
confidence: 84%
“… 16 In addition, we provided robust evidence that vitamin D/vitamin D receptor (VDR) pathway curbs cell apoptosis and pro‐inflammatory cytokine production in oral keratinocytes under inflammatory condition via regulating miRNAs, HIF‐1α signalling and renin levels. 19 , 20 , 21 , 22 , 23 , 24 However, the effect of vitamin D on STING and its downstream cytokines remains an enigma. Here, our data suggest 1,25(OH) 2 D 3 , the active form of vitamin D, decreases STING expression in oral keratinocyte to inhibit IFNβ production under OLP circumstance.…”
Section: Introductionmentioning
confidence: 99%
“…The miRNAs mediate post-transcriptional silencing through partial complementary binding to the 3′un-translated region (UTR) of the target mRNA. Decreased expression of some miRNAs has been observed in immune-mediated inflammatory skin lesions including OLP [ 192 , 193 , 194 ] psoriasis [ 194 , 195 , 196 ], and atopic eczema [ 197 , 198 , 199 , 200 , 201 ] compared to healthy non-lesional skin. In OLP, Wang et al employed HaCaT keratinocytes stimulated with lipopolysaccharide (LPS) to mimic the OLP immune environment and examined, under OLP-like settings, the role of miR-125b in the growth and apoptosis of keratinocytes.…”
Section: Role Of the Pi3k-akt-mtor And Related Network In Skin Develo...mentioning
confidence: 99%
“… 111 , 112 By decreasing VDR expression, miR-122 can improve the apoptosis of oral keratinocytes. 16 In addition, the vitamin D/VDR signaling pathway inhibits the expression of miR-802 in human oral keratinocytes that is stimulated or activated by lip-polysaccharides, thereby inhibiting the apoptosis of OLP cells by blocking the NF-κB signaling pathway. 112 Ge et al 82 found that the expression of miR-27 in OLP is accelerated by vitamin D/VDR signaling.…”
Section: Vitamin D/vdr Signaling Pathwaymentioning
confidence: 99%
“… 15 The apoptosis of keratinocytes may be promoted by miR-122 in OLP. 16 Further, changes in the expression of miR-21 and miR-125a may lead to malignant transformation. 17 In addition, a number of miRNAs show altered expression in OLP.…”
Section: Introductionmentioning
confidence: 99%